Temperature-Dependent Electronic Ground-State Charge Transfer in van der Waals Heterostructures - Park, Soohyung; Wang, Haiyuan; Schultz, Thorsten; Shin, Dongguen; Ovsyannikov, Ruslan; Zacharias, Marios; Maksimov, Dmitrii; Meissner, Matthias; Hasegawa, Yuri; Yamaguchi, Takuma; Kera, Satoshi; Aljarb, Areej; et al. (My University, 2021)
Electronic charge rearrangement between components of a heterostructure is the fundamental principle to reach the electronic ground state. It is acknowledged that the density of state distribution of the components governs the amount of charge transfer, but a notable dependence on temperature is not yet considered, particularly for weakly interacting systems. Here, it is experimentally observed that the amount of ground-state charge transfer in a van der Waals heterostructure formed by monolayer MoS2 sandwiched between graphite and a molecular electron acceptor layer increases by a factor of 3 when going from 7 K to room temperature. State-of-the-art electronic structure calculations of the full heterostructure that accounts for nuclear thermal fluctuations reveal intracomponent electron-phonon coupling and intercomponent electronic coupling as the key factors determining the amount of charge transfer. This conclusion is rationalized by a model applicable to multicomponent van der Waals heterostructures.
Keywords: 2D semiconductors; MoS2; Charge transfer; Electron-phonon coupling; Molecular dopants; Photoelectron spectroscopy